Molecular basis of the glycoprotein-C-negative phenotype of herpes simplex virus type 1 macroplaque strain. - Draper, K G (1984)
The basis for the inability of the macroplaque (MP) strain of herpes simplex virus type 1 to express mature glycoprotein C (gC) was examined. RNA transfer (Northern) blot analysis with hybridization probes from the region of the herpes simplex virus type 1 DNA known to encode the gC gene indicated that gC mRNA was produced in MP-infected HeLa cells at levels relative to other mRNAs comparable with that seen in KOS-infected cells. Comparative nucleotide sequence analysis of the gC gene from the MP and KOS strains, coupled with the results of recently reported marker rescue experiments, indicates that the inability of MP to produce gC is due to a frameshift mutation in the gC-coding sequence. Because two different (out-of-phase) open reading frames overlap the gC-coding sequence in the region of the mutation, MP mRNA can encode two gC-related polypeptides. Two polypeptides of the predicted size and precipitable by anti-gC antibodies were produced by in vitro translation of MP mRNA. These polypeptides have not been detected in extracts from infected cells with the same antibodies. Comparative nucleotide sequence analyses led to several corrections in the published sequence for the gC gene and the 17,800-molecular-weight polypeptide gene just to the right in KOS DNA. These relatively minor effects on the predicted amino code sequence of gC are tabulated.